MATERIALS FOR TEACHING CULTURE REALIA, FILMS, SIGNS. - Nodirbekov Davronbek (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This paper aims to answer the questions of when and how authentic materials should be used in EFL classrooms, and how cultural content may be included in the curriculum. To address these questions, the paper is organized in two parts. In the first part, the definition of authentic materials is given. Then advantages and disadvantages of the use of authentic materials are discussed. In the second part, the definition of culture is given and then, why and how cultural content should be used is discussed.